Reimagining agri-value chains as sites of social and societal reproduction - Bindu, Chandana Rajasekharan (International Rice Research Institute, 2023)
This presentation highlights a 2023 scoping review of literature of studies conducted in Asia, Africa, Latin America and Middle East and North Africa (MENA) focused on the way women’s labor and productivity is conceptualized in the value-chain approach in agri-food systems. The review argues that even in interventions designed to be gender transformative, productivity gains are assessed in terms of extracting more economic value per unit of input factors. They do not consider the nodes as sites of social and societal reproduction and, consequently, ignore the care and affective labor that women perform to maintain them. This is significant because a-economic labor is consequently not considered while calculating total factor productivity and results in potentially false narratives of interventions producing Pareto gains. Some interventions utilize a methodological individualist lens that only considers the behavior of the communities and groups as the aggregate of the behavior of the individuals. Consequently, interventions that may not provide significant benefits at the individual level, but transform social norms, might be categorized as unsuccessful. Together, this results in monitoring and evaluation frameworks that privilege individual economic gains, discounting trade-offs in other forms of non-economic labor or impact on community well-being. The review calls for a framework for a comprehensive evaluation of inputs and outputs, including economic inputs and impact at the community level.